WORKSHOP STRATEGI PEMBIMBINGAN PENGENALAN LAPANGAN PERSEKOLAHAN (PLP) DALAM MENDUKUNG RECOVERY PEMBELAJARAN PASCA-PANDEMI DI SEKOLAH DASAR - Heri Setiawan; A. Wahab Jufri; Dadi Setiadi; Baiq Niswatul Khair (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2022)
The purpose of the service activities that will be carried out is to help students in elementary schools overcome learning loss through personal guidance by PLP participating students to students starting from an initial ability assessment then planning treatment that will be given according to the abilities of each student and assessing the final result of the results of mentoring. The method used in this service is through workshops that are more based on the direct practice of guiding elementary school students to improve their numeracy literacy skills. The service activities are carried out in the following stages: Literature study, teacher needs analysis in the form of teacher understanding and skills in preparing mentoring plans for students who experience learning loss, measuring teacher initial abilities, designing student tutoring programs, conducting workshops: in the form of participant mentoring studies, design practice evaluation instruments, monitoring and guidance in the field by the community service team, assessment of the quality level of implementation and results of participant workshops, and preparation of PPM reports. This training was held on Thursday 22 September 2022 in the Hall of Building A FKIP Mataram University. There were 20 participants, consisting of 5 principals and 15 teachers from 5 elementary schools in the city of Mataram. The activity is carried out in three main stages, namely opening, delivering material, question and answer and practice, and closing. The results of the questionnaire showed an increase in teacher understanding related to the concept of learning loss, numeracy literacy assessment, and steps to handle students affected by learning loss. The workshop activities were also followed up with teacher mentoring activities when guiding PLP participants in their respective schools to carry out learning recovery.